Evaluation of percutaneously adjustable hydraulic urethral sphincters with and without induced mechanical failure. Issue 7 (3rd September 2013) - Tong, Kim; Nelson, Laura L.; Hauptman, Joe; Nelson, Nathan C.
Abstract Objective To describe (1) the radiographic appearance of intact hydraulic urethral sphincters (HUS) and (2) the success of leak detection using clinically feasible methods. Study Design Prospective, blinded in vitro study. Sample Population Thirty HUS devices (10 each of 8, 10, and 12 mm diameter sizes). Materials and Methods All devices were inflated with saline (0.9% NaCl) solution to complete occlusion, inspected, and weighed over a 24‐hour period for manufacturing defects. HUS phantoms were created to mimic surrounding soft tissues. One randomly selected HUS of each size was evaluated radiographically at different inflation volumes and angles. All HUS systems were then evaluated in random order before and after puncture with volumetry, manometry, radiography, and contrast fluoroscopy. Volumetry was the total volume (mL) retrieved from each HUS system. Manometry was the pressure (cm H2O) within each HUS system. The HUS devices were filled to a known volume before each measurement. Results When all HUS sizes were considered, volumetry did not reveal significant differences before and after puncture, but manometry was significantly different (P < .001). Radiography was 63.8% sensitive and 88.3% specific for puncture diagnosis, with inter‐observer agreement of 0.58. Contrast fluoroscopy was 78.4% sensitive and 100% specific, with inter‐observer agreement of 0.97. Conclusions Of those methods tested, contrast fluoroscopy was the most sensitive, specific, and consistent method of leak detection. Manometry was also helpful, but may be difficult to use clinically. Volumetry and radiography were relatively poor indicators of leakage in this model.